(untitled) (Journal of the College of Basic Education, 2023)
In this work ,the wavelengths of light emitted and the amount of intensity from un annealed (v2o5) thin film and it annealed at (100,200) were studied by Raman spectroscopy . In order to study the influence of the annealing on the amount of light intensity emitted from films, the results showed that the amo- unt of light intensity emitted from annealed thin films higher than un annealed thin films and it increased as the temperature annealing increase, studied Atomic Force Microscopy (AFM) of un annealed (v2o5) thin film and annealed (v2o5) thin films at (100,200) where viewed that the surface characteristics changed for it where the crystal structure became butter at thin films annealing where annealed(v2o5) thin films at (200) became brightest and homogenous